2021
DOI: 10.3390/su13148024
|View full text |Cite
|
Sign up to set email alerts
|

Green Logistics Service Supply Chain Games Considering Risk Preference in Fuzzy Environments

Abstract: The increasing pressures from environmental crises are responsible for the green and sustainable choices made in supply chain management. Green logistics service supply chain (LSSC) operations play a significant role in reducing the environmental burden of the supply chain, and the risk preferences of logistics enterprises lead to more uncertainties in the green management of LSSC. Much research has been limited to case studies of green LSSC, and the different combinations of risk preferences among LSSC partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Determining the value of the weights can usually be based on the experience and knowledge of the decision maker, and there are some methods for determining the weights, such as equal weights, minimizing acceptable affiliation, hierarchical analysis, and direct assessment. In this thesis, the most probable value method is used, i.e., 13 16 ww ==, 2 46 w = and 0.5  = . because the possible value of a fuzzy number is usually the most important one, and therefore, a higher weight is assigned.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Determining the value of the weights can usually be based on the experience and knowledge of the decision maker, and there are some methods for determining the weights, such as equal weights, minimizing acceptable affiliation, hierarchical analysis, and direct assessment. In this thesis, the most probable value method is used, i.e., 13 16 ww ==, 2 46 w = and 0.5  = . because the possible value of a fuzzy number is usually the most important one, and therefore, a higher weight is assigned.…”
Section: )mentioning
confidence: 99%
“…At the same time, the quality of economic development is also highly correlated with logistics efficiency. Literature [13] talks about how risk appetite affects the equilibrium behavior between logistics integrators and providers, and the results point out that an appropriately optimistic risk appetite has a certain positive effect on the improvement of logistics efficiency. Literature [14] designed a logistics environmental assessment index for assessing the green logistics performance of 112 countries, and based on the results of the analysis, it was found that the national ecological logistics minutiae index and the logistics performance index were highly positively correlated, and both were significantly affected by the regional economy.…”
Section: Introductionmentioning
confidence: 99%
“…Agrawal and Seshadri [18] used the demand function in the Newsvendor model, and proposed that the function is determined by the form of expected demand and random fluctuation. Wang et al [19] discussed the impact of retailers with different risk preferences on the performance of the green supply chain under the fuzzy environment using fuzzy variables to describe the uncertainty in the distribution process of the green supply chain and considering the different attitudes of decision makers to deal with risks. Choi et al [20] pointed out that the influence of power structure on supply chain may depend on the way demand model is formed.…”
Section: Freight Market Demand Researchmentioning
confidence: 99%
“…Green logistics tries to combine efficient transportation with environmentally friendly urban logistics system (Wang & Hu, 2021).…”
Section: Introductionmentioning
confidence: 99%